Productivity of Bali Cattle on Peatland in Central Kalimantan - Kristyan Amiano; Woro Busono; Sucik Maylinda (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2020)
This study aims to compare the productivity of Bali cattle bred on wet peatland and on dry peatland. This research was conducted in Pulang Pisau Regency, Central Kalimantan Province on September-November 2019. The research method used were a survey, observation and measurement of calf directly in the field. The samples of the area used were four districts using purposive sampling based on the largest population of Bali cattle on dry peatland and wet peatland. The total number of Bali calves were 186 tails. The observations consist of birth weight, weaning weight, and weight gain.The data were processed using the t-test (Independent t-test) with SPSS 2.2. The results obtained that productivity of male calf and female calf were higher productivitiy in dry peatland than wet peatland.